2011
DOI: 10.1007/s00441-011-1258-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave-induced expression of lubricin in tendons and septa

Abstract: Lubricin, a lubricating glycoprotein that facilitates tendon gliding, is upregulated by mechanical as well as biochemical stimuli, prompting this study of its induction by extracorporeal shockwave therapy (ESWT). The objective of this study was to characterize and quantify the effect of ESWT on lubricin expression in tendons and septa in a rat model. Hindlimbs of six rats were treated with low-dose ESWT and those of another six with high-dose ESWT, using contralateral limbs as controls. After 4 days, resected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…As such, ESWT and HAi may have mutually bene cial effects in the treatment of sPFOLP. Whether ESWT can induce gene expression of HA (as demonstrated for lubricin [45], another molecule that serves as lubricant in synovial uid and is decreased in OA [46]) is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As such, ESWT and HAi may have mutually bene cial effects in the treatment of sPFOLP. Whether ESWT can induce gene expression of HA (as demonstrated for lubricin [45], another molecule that serves as lubricant in synovial uid and is decreased in OA [46]) is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the early collagen-degradation effects on exposed tissues, the shock wave exposure on non injured tissue is matter of debate, and the authors stated that it may be advisable to consider a temporary restriction of the physical activities in recently treated patients. In 2011 Zhang et al 19 demonstrated, in a rat model study, that ESWT stimulates endogenous lubricin production in tendons and septa exposed. Clinically, an increased lubricin deposition in tendons and septa following ESWT may contribute to the beneficial effects of ESWT.…”
Section: Experimental Studies On Animal Modelsmentioning
confidence: 99%
“…Animal studies show that ESWT has an influence on pain transmission by acting on substance P, calcitonin gene-related peptide (CGRP) expression in the dorsal root ganglion and on neurovascular sprouting. [9][10][11][12][13][14][18][19][20][21][22][23] ESWT uses biphasic acoustic energy that goes from positive high peak pressures (10-100 MPa (mega pascals) for fESWT;0.1-1 MPa for rESWT) to negative phase (10 MPa); short rise times (10-100 ns for F-ESWT;0.5-1 ms for rESWT), short duration (0.2-0.5 ms for fESWT;0.2-0.5 ms for rESWT). Focused and radial shockwaves are generated in different ways.…”
Section: -14mentioning
confidence: 99%
“…Focused shockwaves are generated electrically, either within the applicator (electrohydraulic technique), or externally to it in the focal zone (electromagnetic or piezoelectric techniques), and then propagate to a designated focal point in order to treat it. Radial shockwaves are ballistic pressure waves generated at lower pressures over a longer time and propagate divergently within the tissue [9][10][11][12][13][14][18][19][20][21][22][23] The induced energy is propagating in the tissue and converges into a focal or radial area, depending on the equipment used and the settings selected for intensity, angle and other parameters. The effect varies, depending on the tissue through which the wave passes and how it absorbs, reflects, refracts or transmits the energy, depending on the specific impedance.…”
Section: -14mentioning
confidence: 99%